Comprehensive phantom for interventional fluorescence molecular imaging - Anastasopoulou, Maria; Koch, Maximilian; Gorpas, Dimitris; Karlas, Angelos; Klemm, Uwe; Garcia-Allende, Pilar Beatriz; Ntziachristos, Vasilis (Journal of Biomedical Optics, 2016)
Fluorescence imaging has been considered for over a half-century as a modality that could assist surgical guidance and visualization. The administration of fluorescent molecules with sensitivity to disease biomarkers and their imaging using a fluorescence camera can outline pathophysiological parameters of tissue invisible to the human eye during operation. The advent of fluorescent agents that target specific cellular responses and molecular pathways of disease has facilitated the intraoperative identification of cancer with improved sensitivity and specificity over nonspecific fluorescent dyes that only outline the vascular system and enhanced permeability effects. With these new abilities come unique requirements for developing phantoms to calibrate imaging systems and algorithms. We briefly review herein progress with fluorescence phantoms employed to validate fluorescence imaging systems and results. We identify current limitations and discuss the level of phantom complexity that may be required for developing a universal strategy for fluorescence imaging calibration. Finally, we present a phantom design that could be used as a tool for interlaboratory system performance evaluation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: interventional fluorescence imaging; intraoperative; phantoms; polyurethane; standardization